The Anatomy of a Premier Business District: An Analysis of Economic Performance and Urban Vitality in Sudirman Central Business District (SCBD), Jakarta - Geraldus Harry Nugraha; Muhammad Sani Roychansyah (Universitas Islam Sultan Agung Semarang, 2026)
This study offers a comprehensive assessment of the Sudirman Central Business District (SCBD) in Jakarta, a leading privately managed superblock. It addresses a research gap in the spatial and economic analysis of elite CBDs in Southeast Asia. A quantitative and descriptive method was used, incorporating geospatial mapping and data on property markets, corporate structures, and public amenities. The results show that SCBD features a highly intensive, vertically integrated mixed-use pattern with a diverse economic structure that supports large corporations and many small businesses. The district functions as a key employment center with excellent public transportation access, boosting urban activity. The study concludes that, although a modern master-planned development, SCBD effectively demonstrates the four core principles of urban vitality identified by Jane Jacobs. These findings inform planning strategies for creating resilient and dynamic business districts in emerging megacities, highlighting that a private sector-driven model within a clear regulatory framework can be an effective development approach.Keywords: Central Business District, Urban Vitality, Economic Performance, Mixed-Use Development, Jakarta.